Black Cat. Vol. 16, The truth about the Tao - Yabuki, Kentaro (Viz Media, 2008)
Train and River put aside their differences as they face off with Shiki, one of the most powerful members of the Apostles of the Stars. Shiki is determined to show that the Tao is the ultimate form of power, and he's going to take down Train, his friends and all of Chronos to prove it!